Divergent genetic architecture of cold stress tolerance in aus and tropical japonica rice - Eizenga, Georgia C.; Santamaria, Yami; Jackson, Aaron K.; Phan, Huy; Jia, Melissa H.; Grunden, Quynh P. - H.; Edwards, Jeremy D.; Himelblau, Ed; Schläppi, Michael R. (Frontiers in Plant Science, 2026)
IntroductionExploring natural genetic variation to facilitate breeding of improved rice seedling cold tolerance will allow the crop to be planted earlier in the growing season, taking advantage of spring rainfall and decreasing exposure to high summer nighttime temperatures, which reduce grain quality.MethodsTo uncover genomic regions in rice that manage cold stress tolerance response mechanisms in the cold-sensitive aus (AUS) and the relatively cold-tolerant tropical japonica (TRJ) subpopulations, and to identify cold tolerance genes, AUS and TRJ recombinant inbred line populations developed from crosses between cold-tolerant and cold-sensitive parents were used for quantitative trait locus (QTL) mapping of two traits: degree of membrane damage after 1 week of cold exposure, quantified as percent electrolyte leakage (EL), and percent low-temperature seedling survivability (LTSS) after 1 week of recovery growth.Results and discussionThirteen subpopulation-specfic QTL were revealed: three EL and four LTSS QTL for AUS, and two EL and four LTSS QTL for TRJ, with no overlap between AUS and TRJ QTL. Only two AUS QTL overlapped with regions previously identified by our AUS × temperate japonica biparental mapping, further confirming the discovery of subpopulation-specific QTL. Based on high-impact genomic differences between the cold-tolerant and cold-sensitive parents, 35 cold tolerance candidate genes were identified—23 in AUS and 12 in TRJ—of which about 50% encode proteins involved in signal transduction and protein homeostasis processes. Although most QTL showed that alleles from cold-tolerant parents improved the two cold tolerance traits, alleles from cold-sensitive parents enhanced these traits at several other QTL. Therefore, alleles from both cold-tolerant and cold-sensitive parents can be used in breeding efforts to generate AUS and TRJ lines with better cold tolerance potential than their respective cold-tolerant parents.